ANALISA PERHITUNGAN HARGA POKOK PRODUKSI DENGAN METODE JOB ORDER COSTING (STUDI KASUS PADA PERABOT SEMANTOK PERKASA BANDA ACEH) - Dewi Maya Sari; Meutia Handayani; Zaharatun Nighisa (Jurnal Penelitian Ekonomi Akuntansi, 2022)
This research examined the Semantok Perkasa Furniture company in Banda Aceh through a case study methodology and descriptive research. The purpose of this study is to create order cost cards and calculate the cost of manufacturing window sills using the job order costing method for Semantok Perkasa Furniture product lines in March 2022. By considering the actual costs incurred, Perabot Semantok Perkasa has never precisely determined the cost of production. The cost of production used to estimate the selling price is simply based on assumptions, thus the cost of raw materials and factory overhead costs cannot be accurately calculated. The findings indicated that there were gaps between the task order costing method and the company's approach for calculating the cost of manufactured goods. Because the cost of manufacturing determined by the company is less than the cost of production determined by the job order costing technique, Semantok Perkasa Furniture is expected to earn extra profit, according to the business's calculations.